The right to housing in the legal orders of the West African states in the light of international human rights protection standards - (:unkn) unknown (My University, 2022)
International law recognizes the right of everyone to an adequate standard of living, including adequate housing. The West African states studied, namely Côte d'Ivoire, Benin, Burkina Faso, Ghana, Mali, Nigeria, Senegal and Togo, have become parties to a number of international treaties that recognize this right. In accordance with the international requirements applicable to them, these States have proceeded to express and implicit constitutional recognition of this right, which is not always without ambiguity. In the same way, their legislation, particularly in the areas of leases, urban planning, land ownership and the civil service, has been quick to assert parts of the right to housing. Despite this, many of their citizens are still not adequately housed in the sense that human rights monitoring bodies understand it. Legislative initiatives are largely devoid of practical effect, so that this right is hardly effective. It can be observed that state judges, whether judicial, administrative or constitutional, have difficulty in protecting the right to housing, or at least fail to protect housing. The indicators even tend to show a degradation of the right to housing, through the continuous degradation of the living conditions of the most vulnerable groups. Faced with this situation, it is necessary to strengthen the normative and more generally legal framework of the right to housing for a better efficiency in the sanction of the violations of the right to an adequate housing.
Keywords: African Research